白令海和西北冰洋海水18O、226Ra及228Ra的示踪研究 - 李琦 (2018)
北冰洋连通着太平洋和大西洋，它对全球淡水收支平衡乃至全球气候变化均产生重要影响。本研究利用中国第6次北极科学考察航次获得的海水δ18O和镭同位素数据，基于S和δ18O的三端元质量平衡关系，计算白令海和西北冰洋河水和海冰融化水的份额，探讨淡水组分和镭同位素的空间分布特征及其与水团性质、海流运动路径的关系，进而计算河水组分从白令陆架至楚科奇陆架，进而输送到加拿大海盆的运移时间。此外，利用1999-2014年间中国第1-6次北极科学考察航次获得的海水δ18O值，评估白令海峡、楚科奇海和加拿大海盆淡水组成的年际变化规律和主要调控因素。 1、白令海淡水组分的空间分布和影响因素。2014年夏季，白令海的. The Arctic Ocean connects the Pacific to the Atlantic Ocean, and has an impact on global freshwater balance and climate change. In this study, oxygen isotopes and radium nuclides in seawater were determined during the 6th Chinese National Arctic Research Expedition in July-September, 2014. The fractions of meteoric water and sea-ice melted water were calculated based on the mass balance of salinit. 学位：理学硕士 院系专业：海洋与地球学院_海洋化学 学号：22320141151309